BRIDGING THE GAP: A CROSS-SECTIONAL QUANTITATIVE STUDY INVESTIGATING ACADEMIC AND SOCIAL SUPPORT SYSTEMS FOR FIRST-YEAR STUDENTS AT MANGOSUTHU UNIVERSITY OF TECHNOLOGY. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background First-year students at Mangosuthu University of Technology (MUT) often encounter academic and social adjustment challenges, impacting performance, sense of belonging, and retention. Academic and social support systems are vital in easing this transition; however, empirical evidence evaluating their effectiveness is limited. This study investigates the availability, accessibility, engagement level, and perceived impact of these support systems on first-year students’ academic success and social integration. Methods A cross-sectional quantitative design was employed using a structured questionnaire distributed to 200 first-year students across five faculties at MUT. Stratified random sampling ensured representation across gender, faculty, and residence status. The survey instrument comprised Likert-scale items assessing experiences with academic support (e.g., tutoring, mentoring) and social support (e.g., peer networks, counselling). Descriptive statistics were used to determine engagement levels and barriers, while Pearson correlation examined relationships between support engagement, academic performance, and satisfaction. Results Of the 200 students surveyed, 176 completed the questionnaire (response rate: 88%). Respondents were 56% female and 44% male; 62% resided in campus residences and 38% commuted. Seventy-two percent engaged with at least one academic support service, while 59% accessed social support. Common barriers included lack of awareness (41%), inconvenient service times (28%), and stigma around counselling (19%). A moderate positive correlation (r = 0.48, p < 0.01) was observed between support engagement and academic performance. High engagement is also aligned with stronger social integration and academic confidence. Conclusion Support systems positively influence first-year student outcomes; however, gaps in awareness and access remain, particularly for off-campus students. Recommendation MUT should enhance visibility and accessibility of support services through targeted orientation, peer mentoring, and early intervention programs to better support first-year student integration and success.